Optimalisasi Media Sosial Untuk Media Relation : Studi Kasus Penggunaan Instagram Oleh Kpid Sumsel - Fadel Alrsyie, M Alif; Saputra, Sepriadi (Komunika : Jurnal Ilmiah Komunikasi, 2025)
In the digital era, social media has become a primary tool for public institutions to build effective relationships with the public and the media. This study aims to understand the optimization of Instagram usage by the Regional Indonesian Broadcasting Commission (KPID) of South Sumatra in conducting media relations activities. Employing a qualitative approach through a case study method, data were collected via in-depth interviews with Instagram account administrators, direct observation of account activities, and analysis of documents including content archives and platform insight data. The findings reveal that KPID South Sumatra has utilized various Instagram features such as feeds, stories, reels, and live sessions to deliver broadcasting supervision information, regulatory education, and activity reports in a visual and dynamic manner. However, several challenges persist, including inconsistent posting schedules, low follower interaction rates, and unstructured digital communication strategies. The optimization efforts remain spontaneous and have not fully leveraged insight analytics for content adjustment. This research recommends the development of more targeted digital communication strategies, encompassing thematic content planning, enhanced audience responsiveness, and social media management team training. Consequently, Instagram can serve as a more effective tool in supporting transparency, accountability, and closeness between KPID South Sumatra and the public as well as broadcasting media. The results of this study are expected to serve as a reference for other regional supervisory institutions in maximizing social media for sustainable and widely impactful media relations activities.